The Correlation Between Stress Levels and Acne Vulgaris Stage in 2016th Students Faculty of Medicine Universitas Airlangga Surabaya - Cita Rosita Sigit Prakoeswa; Etty Hary Kusumastuti; Nadya Divina Baihaqi (Health Notions, 2021)
Introduction: Acne vulgaris is a common cutaneous inflammatory disorder affecting more than 85% of adolescents worldwide. More than quarter of medical students 2016th had suffers from acne and complaint stress. The stress levels could increase because lot of burden in academy assessment, and other factors that can induced stress like psychosocial psychological stress and triggers by other factors. Stresss levels measured by PSS questionnaire there is mild (≤ 13), moderate (14-26) and severe (>27). Although there is widespread acceptance of a relationship between stress and acne flares, not many studies have been conducted to assess this relationship. Therefore this research encourage, does the stress affect with the severity appearances of acne. Objectives: To correlate stress levels to acne vulgaris stage among students of Faculty of Medicine Universitas Airlangga. Methods: This research design used correlative analysis with cross sectional aproach and total sampling of all students medical students 2016th with the exclusion of students who are using corticosteroid, psychotherapy drugs and non acne vulgaris by staging the acne vulgaris using GAGS and stress level using PSS (perceived stress scale) questionnaires that relate to the research. Also taking pictures for assure the stage of respondent who suffers acne vulgaris, measure and correlate with spearmen correlation. Results: The total of subjects 69 students constituted the study population. This study was attended by 60 male 27,6% of the total number of respondents and 157 female 72,4%. There is 69 people who suffered from acne consist of 46 peoples 66,67% had mild acne stage, 17 peoples 24,63% had moderate acne stage and 6 peoples 8,7% had severe acne stage. The risk factor that mostly induced acne vulgaris stage were final exam (91.3%), eating habbit(87%), and premenstruation acne(71%). The correlation between stress levels and acne vulgaris stage shows .521 using SPSS program. Conclusion: There is significant correlation that the stress levels effect to the skin apearrance and stage of acne vulgaris, also the others factors have been asked on the questionnaire could be increase the acne become more aggressive growth on skin.Keywords: acne vulgaris stage; medical students; stress levels